1999
DOI: 10.1002/(sici)1521-1878(199901)21:1<38::aid-bies5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative calcium entry channels

Abstract: In the phospholipase C signaling system, Ca2+ is mobilized from intracellular stores by an action of inositol 1,4,5‐trisphosphate. The depletion of intracellular calcium stores activates a calcium entry mechanism at the plasma membrane called capacitative calcium entry. The signal for activating the entry is unknown but likely involves either the generation or release, or both, from the endoplasmic reticulum of some diffusible signal. Recent research has focused on mammalian homologues of the Drosophila TRP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
219
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(225 citation statements)
references
References 76 publications
6
219
0
Order By: Relevance
“…Recent data suggest that there might be a direct molecular interaction between components of the intracellular stores (such as the IP 3 receptor itself) and plasmalemmal TRP channels (see Putney & Mckay, 1999). However, there is the possibility that Ca 2+ released by CPA could activate phospholipid hydrolysis and produce second messenger(s) (Matkovich & Woodcock, 2000).…”
Section: British Journal Of Pharmacology Vol 133 (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that there might be a direct molecular interaction between components of the intracellular stores (such as the IP 3 receptor itself) and plasmalemmal TRP channels (see Putney & Mckay, 1999). However, there is the possibility that Ca 2+ released by CPA could activate phospholipid hydrolysis and produce second messenger(s) (Matkovich & Woodcock, 2000).…”
Section: British Journal Of Pharmacology Vol 133 (2)mentioning
confidence: 99%
“…Though a number of ion channels have been implicated in such in¯ux, the role of L-type voltage gated Ca 2+ channels in human ASM seems to be a relatively minor one. Attention has been recently drawn to store-operated Ca 2+ channels (SOC) which are activated upon emptying of IP 3 -dependent Ca 2+ stores (Putney & Mckay, 1999), and to a variety of channels directly activated by second messengers such as Ca 2+ , IP 3 , IP 4 , arachidonic acid and its metabolites (for review see Kiselyov & Muallem, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the last case, store-operated Ca 2ϩ entry (SOCE) is triggered by depletion of SR Ca 2ϩ stores (6,41,42,49,55,56). We and others have shown that different transient receptor potential channel (TRPC) isoforms are expressed in ASM (6,58).…”
mentioning
confidence: 99%
“…The mechanism for Ca 2ϩ entry has been studied extensively. In one mechanism, termed "store-operated Ca 2ϩ entry," the emptying of intracellular stores activates surface membrane Ca 2ϩ channels via either diffusible factors or a direct interaction between IP 3 receptors and surface Ca 2ϩ channels (55)(56)(57). These Ca 2ϩ -permeable channels on the cell surface are called store-operated channels (SOC).…”
Section: Role Of Trp In Plc-dependent Ca 2ϩ Influxmentioning
confidence: 99%